2021
DOI: 10.22435/spirakel.v12i2.3442
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Yang Berhubungan Dengan Perilaku Minum Obat Dalam Pemberian Obat Pencegahan Massal Filariasis Di Kabupaten Banyuasin Tahun 2015

Abstract: Filariasis adalah penyakit infeksi yang disebabkan oleh Wuchereria bancrofti, Brugia malayi, dan Brugia timori, yang menyebabkan cairan getah bening tersumbat dan bengkak pada kaki dan lengan. Eliminasi filariasis dilakukan melalui program pemberian obat pencegahan massal kepada seluruh penduduk di daerah endemis setahun sekali selama lima tahun. Kabupaten Banyuasin telah mengalami penurunan angka prevalensi mikrofilaria. Namun risiko penularan masih terjadi karena kasus baru ditemukan setelah periode ketiga p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The results of the research conducted by Ritawati et al in Banyuasin Regency in 2015 revealed that the scope of behavior for taking filariasis mass prevention drugs was significantly influenced by four factors, one of which was knowledge (p = 0.001). 9 A similar study by Isabela et al in 2017 found that the determinants of adherence to taking anti-filariasis drugs were age (p = 0.016), sex (p = 0.002), education (p = 0.041), knowledge (p = 0.043), the role of health workers (p = 0.043), and the role of community leaders (p = 0.044). 10 Meanwhile, the research conducted by Yuziani et al in Baktiya Subdistrict, North Aceh showed different results from the aforementioned research which stated that there was no relationship between the level of knowledge and adherence to filariasis mass treatment(p value = 0.996).…”
Section: Introductionmentioning
confidence: 82%
“…The results of the research conducted by Ritawati et al in Banyuasin Regency in 2015 revealed that the scope of behavior for taking filariasis mass prevention drugs was significantly influenced by four factors, one of which was knowledge (p = 0.001). 9 A similar study by Isabela et al in 2017 found that the determinants of adherence to taking anti-filariasis drugs were age (p = 0.016), sex (p = 0.002), education (p = 0.041), knowledge (p = 0.043), the role of health workers (p = 0.043), and the role of community leaders (p = 0.044). 10 Meanwhile, the research conducted by Yuziani et al in Baktiya Subdistrict, North Aceh showed different results from the aforementioned research which stated that there was no relationship between the level of knowledge and adherence to filariasis mass treatment(p value = 0.996).…”
Section: Introductionmentioning
confidence: 82%
“…This study used a spreadsheet instrument which was a modification of the "Data Quality Assessment for Neglected Tropical Diseases: Guidelines for Implementation, Working Draft September 2013" method developed by WHO and ENVISION/RTI [6]. The tool was a spreadsheet program that uses the EWARS data quality evaluation approach for reporting.…”
Section: Data Collectionmentioning
confidence: 99%